Click chemistry-based imaging to study the tissue distribution of the curcumin–protein complex in mice. Issue 2 (10th February 2020) - Zhou, Jingyi; Wang, Weicang; Zhang, Jianan; Du, Zheyuan; Yang, Haixia; Zhang, Guodong
Abstract : Using click chemistry-based fluorescence imaging, here we show that curcumin, a bioactive dietary compound with a thiol-reactive α, β-unsaturated carbonyl moiety, can covalently modify protein thiols in colon and liver tissues in mice. Abstract : Previous studies have shown that curcumin, a bioactive dietary compound with a thiol-reactive α, β-unsaturated carbonyl moiety, can covalently modify protein thiols. However, most of the previous studies were performed in cultured cells or cell-free enzyme systems, and so it remains unknown whether curcumin could covalently modify proteins after oral administration in vivo . Using click chemistry-based fluorescence imaging, here we show that oral administration of dialkyne-curcumin (Di-Cur), a "click" probe mimicking curcumin, results in covalent modifications of cellular proteins in colon and liver tissues, but not in other tissues, in mice. This result suggests that oral administration of curcumin leads to the formation of the curcumin–protein complex in a tissue-specific manner, which could contribute to the biological effects and/or pharmacokinetics of curcumin. Further studies to elucidate the identities of curcumin-binding proteins could greatly help us to better understand the molecular mechanisms of curcumin, and develop novel strategies for disease prevention.